ANALISIS PERLAKUAN AKUNTANSI PERSEDIAAN OBAT-OBATAN (Studi Kasus pada Rumah Sakit Umum Daerah Kabupaten Kediri) - Lela Tri Ratnasari; Rizka Fitriasari (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research aims to know registry and estimation system of the medicines supply at Local Hospital in Kediri Regency have been appropriate to the Statement of Government Accounting Standard (PSAP) Number 05 year of 2010. All in all, accounting treatment of PSAP 2010 have been explained well enough in RSUD of Kediri Regency. From the analysis result, the researcher identifies that much appropriateness between the accounting treatment which has been arranged in PSAP 2010 with an accounting policy which has been applied in the element of financial report and accounting treatment of supply used. However, in some treatments, there is inappropriateness to PSAP 2010 which concerns to accounting treatment of supply.